Impact of green stadium initiatives on donor intentions toward an intercollegiate athletic programme. (1st January 2011) - Jin, Liyan; Mao, Luke Lunhua; Zhang, James J.; Walker, Matthew B.
The purpose of this study was to investigate the relationship among potential athletic donors' beliefs, attitudes, subjective norms, and perceived behavioural control on donor intentions toward green stadium initiatives (GSI). Research participants were university students (N = 186) who responded to a questionnaire designed to measure these related concepts. Hierarchical regression analyses revealed that attitude and subjective norm mediated the impacts of behavioural beliefs and normative beliefs on donor intentions toward GSI. These findings support the applicability of the theory of reasoned action (TRA) in nurturing donation behaviours in the collegiate athletic context. The discussion is focused on developing educational and promotional programmes to enhance beliefs, generate positive attitudes, and develop supportive norms. Implications for practitioners are further presented.